Banana transshipment model - Brasington, John (Kansas State University, 2012)
Bananas are the number one selling produce item in the grocery store. On average, bananas account for 6% of produce department sales and 1% of total grocery store sales. According to The Packer’s “2010 Fresh Trends”, 88% of consumers in all categories purchase bananas. Also, 94% of consumers in the study purchased bananas within the last twelve months. Over the last decade, fuel prices have increased to a point where logistics and shipping have become more important than ever to the banana industry. This logistics challenge is compounded because there are no bananas grown in the United States and the fruit has to be shipped from around the world. Fuel is used at high rates via the ocean cargo and trucking shipments to meet yearly demand. To manage these logistical challenges, this thesis analyzes the optimal shipping route for bananas arriving to the west coast from Central and South America to various markets using a transshipment model. The goal of the transshipment model estimates the supply chain that creates the lowest cost. Through analysis of fuel, trucking, and shipping markets, the model makes the optimal decision regarding transportation routing. The model is limited to transportation costs only. However, items such as fruit costs and other additional up charges could be analyzed.
Keywords: Banana trade; Network flow model; Transportation costs; Dole food company